Joint intelligent optimization design of the active region and electron blocking layer for AlGaN-based deep ultraviolet LEDs - Jinglei Wang; Huimin Lu; Jianhua Ma; Yifan Zhu; Zihua Zhang; Tongjun Yu; Xuecheng Wei; Hua Yang; Jianping Wang (AIP Advances)
Aiming to enhance the internal quantum efficiency (IQE) of AlGaN-based deep ultraviolet light-emitting diodes (DUV LEDs), the active region based on the V-shaped quantum well (QW) and the electron-blocking layer (EBL) structure are jointly optimized using intelligent algorithms in this work. This method focuses on maximizing the IQE of the DUV LEDs by optimizing the geometric and material parameters of multiple QWs (MQWs) and EBL. It is demonstrated that the DUV LED with an optimized structure exhibits smaller band edge tilt for improved wave function overlap in QWs and more effective carrier blocking for reduced electron overflow compared to that with a conventional structure. The results show that, by optimizing the active region and EBL structure using the proposed method, the IQE and maximum radiation intensity of the AlGaN-based DUV LED are enhanced by 38% and 41% at 200 A/cm2 injection current density, respectively.